Nutrition in Pediatric Extracorporeal Membrane Oxygenation: A Narrative Review - Toh, Theresa S. W.; Ong, Chengsi; Mok, Yee Hui; Mallory, Palen; Cheifetz, Ira M.; Lee, Jan Hau (Frontiers in Nutrition, 2021)
Extracorporeal membrane oxygenation (ECMO) support is increasingly utilized in quaternary pediatric intensive care units. Metabolic derangements and altered nutritional requirements are common in critically ill children supported on ECMO. However, there remains no consensus on the optimal approach to prescription of nutrition in these patients. This narrative review aims to summarize the current medical literature on various aspects of nutrition support in pediatric patients on ECMO. These include: (1) nutritional adequacy, (2) pros and cons of feeding on ECMO, (3) enteral versus parenteral nutrition, and (4) proposed recommendations and future directions for research in this area.